3x-(-6)=36

Simple and best practice solution for 3x-(-6)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(-6)=36 equation:


Simplifying
3x + -1(-6) = 36

Multiply -1 * -6
3x + 6 = 36

Reorder the terms:
6 + 3x = 36

Solving
6 + 3x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3x = 36 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 36 + -6
3x = 36 + -6

Combine like terms: 36 + -6 = 30
3x = 30

Divide each side by '3'.
x = 10

Simplifying
x = 10

See similar equations:

| .5(2n+6)=4(n-3) | | 48r=12 | | 2x-3=6x-17 | | 0.25d=130 | | -8+4k=16 | | -42=-6b | | 5x^2-20x=10 | | 2(3a+12)=3(4a+2) | | 3c=-18 | | y^2+18y+32=226 | | 6x+5=2x-11 | | t-19=-2(t+5) | | z-6=-10 | | v^2-20v+19=0 | | p-22=3(2p-4) | | 6x-5=2x-11 | | -4+a=15 | | 6x+7y=13 | | 12x+5=8x+13 | | 2y-6=9-3y | | w^2+6w=-3 | | log(y)=1.6 | | 4=m+19 | | 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 |

Equations solver categories